Effects of High-Fat Diet During Childhood on Precocious Puberty and Gut Microbiota in Mice - Bo, Tingbei; Liu, Min; Tang, Liqiu; Lv, Jinzhen; Wen, Jing; Wang, Dehua (Frontiers in Microbiology, 2022)
A high-fat diet (HFD) affects metabolism through gut microbiota, while the relationship between gut microbiota and precocious puberty is still unclear. The model of precocious puberty was established by feeding female mice with a high-fat diet from 21 days old. After starting puberty, the serum hormone levels, gut microbiome sequencing, and metabolomics were collected. DNA was extracted from fecal material, and the V3-V4 region of the bacterial 16S rRNA gene was amplified, followed by microbial composition analysis. Subsequently, associations between precocious puberty and the microbiota were determined. We found that: 1. HFD after weaning caused precocious puberty, increased serum leptin, deoxycholic acid； 2. Through correlation analysis, we found that Bilophila was negatively correlated with the days of the vaginal opening in mice, and positively correlated with hypothalamic GnRH and serum leptin, suggesting that Bilophila may have a role in promoting sexual development. 3. “HFD-microbiota” transplantation promoted the precocious puberty of mice. Therefore, the change of gut microbiota can slow down precocious puberty and early mating behavior, which is conducive to animal growth.